ANALYZING STUDENT MOTIVATIONS FOR SELECTING PGMI AS THEIR MAJOR - Darmiah Darmiah; Tria Marvida (PIONIR: JURNAL PENDIDIKAN, 2024)
This study examines the motivations behind students’ choices to pursue a major in Primary Islamic Education Teacher Training (PGMI) at the Faculty of Tarbiyah and Teacher Training, UIN Ar-Raniry Banda Aceh. PGMI aims to prepare graduates with competencies in foundational Islamic education and child development, equipping them to be creative, productive, and independent educators. Given the varied internal and external motivations influencing student decisions, understanding these motivations is essential, as they play a crucial role in academic success and career satisfaction. Accurate choice of major can significantly impact student achievement and future opportunities, while an inappropriate choice may hinder career potential. Employing a quantitative, descriptive-exploratory approach, this study seeks to answer the question, "What motivates students to choose PGMI as their major?" Participants included PGMI students from the 2019 cohort at UIN Ar-Raniry Banda Aceh. Data collection involved questionnaires and observations, with results analyzed through descriptive statistics. Findings revealed two primary motivational factors influencing students’ choice of PGMI: (1) a strong aspiration to become teachers and (2) respect for parental expectations. This research contributes insights into student motivation, supporting universities in aligning programs with student interests and career goals. Keywords: Student Motivation, Madrasah Ibtidaiyah Teacher Education, PGMI, Major Selection, Faculty of Tarbiyah and Teacher Training, UIN Ar-Raniry, Career Motivation